Meningkatkan Kualitas Pembelajaran Baca Tulis Qur’an (BTQ) Melalui Bimbingan Belajar Tahsin di SDN Wanawali - Ryan Apriansyah; Yuwan Fijar Anugrah; Dyah Wulandari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Al-Qur'an education in Indonesia, as a majority Muslim community, should receive primary attention. However, the reality on the ground shows that Al-Qur'an teaching does not receive adequate time allocation in the curriculum, causing many students to have difficulty reading and writing the Qur'an. The Al-Qur'an Reading and Writing (BTQ) program using the tahsin tutoring method is a solution with a significant impact that can be felt. This research uses the PAR (Participatory Action Research) research method, which is defined as researchers participating and taking action directly in community service activities. This research is a Community Service Activity which aims to help students and teachers at SDN Wanawali overcome the problem of learning the Al-Qur'an. Using the Tahsin Tutoring method, as part of the Al-Qur'an Reading and Writing Program. This research includes the stages of location survey, observation, planning, implementation and evaluation. The subjects of this research were students in grades 5 and 6 of SDN Wanawali, Cibatu District, Purwakarta Regency, starting on 16 – 23 February 2024. The research results showed that Tahsin Tutoring activities succeeded in increasing students' enthusiasm in learning to read, write and memorize the Al-Qur'an. The Iqra book sorogan method, short surah reading tests, and memorization quizzes provide an interactive and interesting learning experience. Grade 5 and 6 students showed improvements in Al-Qur'an skills, while PAIBP teachers at SDN Wanawali became more creative in delivering learning material.